2015
DOI: 10.1016/j.jnucmat.2014.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Transient heating effects on tungsten: Ablation of Be layers and enhanced fuzz growth

Abstract: A pulsed laser in the PISCES-B facility is used to simulate transient heating events such as ELMs and disruptions on W. The first study of enhanced nano-scale W tendril growth ("fuzz") due to cyclic fast transient heating of W exposed to low energy (+ He E~30 eV) He + ions is presented. Fuzz due to transient heating is up to ~10x thicker than the steady state fuzz thickness with no laser heating. A general thermal activation model yields higher values for the activation energy and pre-exponential factor than p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Significantly enhanced fuzz growth rate has been observed when the W sample was exposed to transient heating by 1-ms-wide 1-Hz laser pulses during plasma exposure (Yu et al 2015), resulting in up to 10× greater fuzz thicknesses after 2800 laser cycles in target regions where peak temperatures reached about 2000 K. At higher peak temperatures (i.e. above 2000 K) negligible fuzz is observed as tendril reintegration or annealing into the W bulk completely dominates growth.…”
Section: Nanofuzzmentioning
confidence: 99%
“…Significantly enhanced fuzz growth rate has been observed when the W sample was exposed to transient heating by 1-ms-wide 1-Hz laser pulses during plasma exposure (Yu et al 2015), resulting in up to 10× greater fuzz thicknesses after 2800 laser cycles in target regions where peak temperatures reached about 2000 K. At higher peak temperatures (i.e. above 2000 K) negligible fuzz is observed as tendril reintegration or annealing into the W bulk completely dominates growth.…”
Section: Nanofuzzmentioning
confidence: 99%
“…This is because the necessary conditions shown in 7 , regarding the temperature and the incident ion energy, may not be satisfied in so-called detached or partially detached regimes. In such regimes, the electron temperature is much less than 10 eV around the strike point; however, the effects of ELMs have yet to be fully understood and can enhance the fuzz growth 26 . For industrial application, it has been shown that the same structures can be grown in commercially available magnetron sputtering devices 27 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The incident He ion energy near the strike point of ITER divertor would be lower than the threshold (∼20 eV) for fuzz formation . However, several recent experiments conducted to investigate transient effects on a W surface have revealed that fuzz growth could be accelerated by adding pulsation to the heat load or incident ion energy . Low‐energy He ions, whose incident energy is lower than 10 eV, are especially likely to contribute to the further growth of fuzz when combined with cyclic precipitation of high‐energy ions .…”
Section: Introductionmentioning
confidence: 99%